Pacing strategies by age in marathon cross-country skiing - Nikolaidis, P. T.; Knechtle, B. (The Physician and Sportsmedicine, 2018)
Objectives: Pacing strategies have mainly been investigated for runners, but little is known for cross-country skiers. The aim of the present study was to investigate whether differences in pacing strategies do exist between younger and older cross-country skiers competing in the 42 km `Engadin Ski Marathon`.